Periostin in the Cancer Stroma of Mycosis Fungoides Palmaris et Plantaris: A Case Report and Immunohistochemical Study - Tanita, Kayo (Case Rep Dermatol, 2016)
Mycosis fungoides palmaris et plantaris (MFPP) is a rare variant of mycosis fungoides limited to the palms and soles. Although little is known about the pathogenesis of MFPP, this variant of mycosis fungoides presents a relatively good prognosis. In this report, we describe an 85-year-old Japanese man with MFPP. Immunohistochemical staining revealed the dense deposition of periostin in the cancer stroma, as well as infiltration of CD163(+)CD206(−) tumor-associated macrophages (TAMs), which suggested the phenotypes of TAMs were not polarized to the M2 phenotype in the lesional skin of MFPP. Our present case might suggest one of the possible reasons for the good prognosis of MFPP.